Photochemical changes in absorption and fluorescence of DDM-containing epoxies. (25th April 2018) - Toivola, Ryan; Jang, Sei-Hum; Mannikko, Donald; Stoll, Stefan; Jen, Alex K-Y.; Flinn, Brian D.
Abstract: Photochemical changes in the optical characteristics of solid polymers form the basis for many important technologies, but few examples are demonstrated in diamine-cured epoxy, one of the most important structural polymer systems. We have observed that diamine-cured epoxies containing the 4, 4′-diaminodiphenyl methane (DDM) framework display changes in both absorption and fluorescence in response to UV light. The change from original "blue" to photo-activated "red" emission can be accomplished by illuminating samples of DDM-containing epoxy with photons of 254 nm or 370 nm wavelengths, followed by excitation of the newly-generated red-emitting fluorophore with 350–400 nm light. Studies of the monomer constituents and of many formulations of diamine-cured epoxy identify the DDM structure as the responsive moiety, both from the epoxy or diamine monomer. The fluorescence change is accompanied by the formation of orange and green chromophores; the orange chromophore is the fluorophore, with a broad 410 nm excitation and 607 nm emission. Our work shows the "blue-to-red" transition to be irreversible and independent of atmospheric oxygen; the fluorophore's impermanence with time and its radical spectral signature identify it as a reactive intermediate rather than a photo-oxidation product. The central methylene radical of the benzoidal DDM structure is proposed as a red-emitting fluorophore/orange chromophore, with the green chromophore being a quinoidal methine resulting from the DDM radical. Graphical abstract: First report of photochemically generated fluorescence changes in solid epoxies. Image 1 Highlights: Diaminodiphenylmethane (DDM)-containing epoxies show "blue-to-red" change in fluorescent emission due to UV illumination. The "blue-to-red" change is irreversible and oxygen-independent. The red emission is impermanent and due to emissive radical on the DDM core. Red fluorescence accompanied by orange and/or green chromophores assigned to benzoidal radical and quinoidal methine.